Automatic Chicken Coop Cleaner - Rajabunesha Anwar Din; Muhammad Azri Suzaimi Shuhaidie (Emerging Advances in Integrated Technology, 2025)
The automatic chicken coop cleaner is designed to sustain hygiene for small scale poultry breeders. This system is developed using an ESP8266 NodeMCU V3 microcontroller which features both scheduled and trigger remote cleaning via Blynk application supported when needed. Manual cleaning is time-consuming, inconsistent, and frequently neglected, particularly among breeders who balance poultry keeping with full-time employment or other responsibilities. Accumulated waste leads to increased moisture, ammonia buildup, and pathogen growth. Poor hygiene contributes to respiratory infections, reduced growth performance, and increased mortality. The cleaning mechanism is driven by a linear actuator and a scraper blade, programmed to operate on a fixed schedule twice daily. The prototype with dimensions of 2feet by 2feet is optimized for 5 to 10 chicks aged 1 to 4 weeks which crucial period for immune system development. The complete cleaning process involves scraper movement forward and backward and took approximately 160seconds. Execution results demonstrate reliable cleaning performance according to the fixed schedule and consistent remote responsiveness via the Blynk application and notification will be sent. Obstructions able to be detected by the system and failure notifications are sent through both the smartphone and email to facilitate timely intervention. The overall system provides a low cost, energy efficient and smart solution that improves flocks’ health, supports operational efficiency and promotes sustainable management.